2016
DOI: 10.18006/2016.4(1).109.115
|View full text |Cite
|
Sign up to set email alerts
|

Water quality in aquaculture and non-aquaculture sites in Taal lake, Batangas, Philippines

Abstract: Aquaculture activities are often blamed for the degradation of water quality of aquatic ecosystem. Present study was conducted to determine the water quality of Taal Lake at two different study sites viz. one under intense fish cage farming activities and the other without aquaculture activities. The study aims to assess the effect of aquaculture activities on selected water quality parameters, which include transparency, temperature, pH, nitrates, phosphates, salinity, total dissolved solids (TDS) and dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The survival rate in the present study did not differ between feed treatments in both species but was relatively low in O. niloticus in comparison to percentage survival achieved in other studies at more than 85% (Abou-Zied 2015; Ammar et al 2008). The low survival rate may be attributed to the low mean dissolved oxygen levels in the experimental sites during the study period, which is typical of the dissolved oxygen level in the cage zones in Taal Lake (Querijero and Mercurio 2016). During these periods of low dissolved oxygen, inappetence, and mortality were recorded.…”
Section: Discussionmentioning
confidence: 93%
“…The survival rate in the present study did not differ between feed treatments in both species but was relatively low in O. niloticus in comparison to percentage survival achieved in other studies at more than 85% (Abou-Zied 2015; Ammar et al 2008). The low survival rate may be attributed to the low mean dissolved oxygen levels in the experimental sites during the study period, which is typical of the dissolved oxygen level in the cage zones in Taal Lake (Querijero and Mercurio 2016). During these periods of low dissolved oxygen, inappetence, and mortality were recorded.…”
Section: Discussionmentioning
confidence: 93%
“…Native to southeastern Asia (Table 1), the said taxon is a hardy tropical fish that can survive a wide range of water conditions. They can thrive in brackish waters with up to 18 ppt salinity, which is higher than in Lake Taal (0.8-0.9 ppt) (GISD 2019;Querijero and Mercurio 2016). It is known that this taxon can tolerate hypoxic waters with up to 0.98 mg/L dissolved oxygen (DO), which is far from 4mg/L, the lowest recorded DO in Lake Taal, which can be observed in the months of January-February when the phytoplankton die-off in the lake (Tripathi et al 2013;Querijero and Mercurio 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Water quality degradation: Water quality degradation in ecosystems that support aquaculture is still a main issue in the Philippines, especially in Luzon. For example, in Taal Lake, concentrations of phosphates, nitrates, and total dissolved solids were significantly higher in aquaculture cage sites than in areas without aquaculture activities (Querijero & Mercurio, 2016;Cruz et al, 2019). Furthermore, the current status of Manila Bay revealed that the levels of PO4 -3 (1.02 mg/L -2.42 mg/L) and NH3-N (0.90 mg/L -2.35 mg/L) were unsuitable for fish culture, although other important parameters like temperature, dissolved oxygen, pH, etc.…”
Section: Challenges In the Philippine Aquaculturementioning
confidence: 99%